Pengaruh Pelatihan Kerja, Kompensasi Finansial, dan Pengembangan Karir terhadap Kinerja Karyawan: (Studi Kasus pada Karyawan Brand Cotton on Cabang Lippo Mall Puri) - Vinna Aprilia Bahri; Setyani Dwi Lestari (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the effect of job training, financial compensation, and career development on employee performance at Brand Cotton On, Lippo Mall Puri branch. The population in this study consisted of 40 employees who served as respondents in completing the questionnaire. The research data were collected using a Likert scale questionnaire, which was then processed and analyzed using Microsoft Excel 2018 and SPSS version 25 software. The research method employed was multiple linear regression, aiming to determine the extent to which each independent variable influences the dependent variable, namely employee performance. The results of this study indicate that job training has a significant effect on improving employees’ abilities and productivity. Financial compensation also has a significant impact on employee performance, as it serves as motivation and encouragement in carrying out work tasks. In addition, career development contributes positively to performance improvement through promotion opportunities and skill enhancement. Overall, these three variables play an important role in achieving optimal employee performance. Therefore, the management of Cotton On Lippo Mall Puri is expected to continuously improve the quality of job training programs, provide fair financial compensation, and offer sustainable career development opportunities for all employees.